Central bank purchases of government bonds - Samuel Huber; Jaehong Kim (University of Zurich, Department of Economics, 2015)
We develop a microfounded model, where agents have the possibility to trade money for government bonds in an over-the-counter market. It allows us to address important open questions about the effects of central bank purchases of government bonds, these being: under what conditions these purchases can be welfare-improving, what incentive problems they mitigate, and how large these effects are. Our main finding is that this policy measure can be welfare-improving, by correcting a pecuniary externality. Concretely, the value of money is increased as central bank's purchases of government bonds induce agents to increase their demand for money, which is welfare-improving.
Keywords: E31; E40; E50; G12; 330; Monetary theory; over-the-counter markets; quantitative easing; money demand; pecuniary externality